2005
DOI: 10.1093/jxb/eri290
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid regulation of heterophylly in Marsilea quadrifolia L.: effects of R-(−) and S-(+) isomers

Abstract: The plant hormone abscisic acid (ABA) induces a developmental switch in the aquatic fern Marsilea quadrifolia, causing the formation of aerial type characteristics, including the elongation of petioles and roots, a change in leaf morphology, the expansion of leaf surface area, and the shortening of the internodes. A number of ABA-responsive heterophylly (ABRH) genes are induced early during the transition. Using optically pure isomers of ABA, it was found that both the natural S-(+)-ABA and the unnatural R-(-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 47 publications
2
41
1
1
Order By: Relevance
“…In general, (2)-ABA has been found to be as effective as (1)-ABA. Experiments with the aquatic fern Marsilea quadrifolia suggest that (2)-ABA is either intrinsically active or its activity is caused by the stimulation of (1)-ABA biosynthesis (Lin et al, 2005). reported that the expression of AtMYB44 was not induced by (1)-ABA, but we observed that it was rapidly induced by (6)-ABA.…”
Section: Discussionmentioning
confidence: 54%
“…In general, (2)-ABA has been found to be as effective as (1)-ABA. Experiments with the aquatic fern Marsilea quadrifolia suggest that (2)-ABA is either intrinsically active or its activity is caused by the stimulation of (1)-ABA biosynthesis (Lin et al, 2005). reported that the expression of AtMYB44 was not induced by (1)-ABA, but we observed that it was rapidly induced by (6)-ABA.…”
Section: Discussionmentioning
confidence: 54%
“…In submerged liverworts, ABA enables the organism to occupy the terrestrial environment. This resembles the induction of terrestrial leaves in the heterophyllous water fern (Marsilea quadrifolia, Lin et al 2005) and angiosperms (Proserpinaca intermedia, Kane and Albert 1982; Ranunculus flabellaris, Young et al 1987;Potamogeton nodosus, Gee and Anderson 1998;Hippuris vulgaris, Goliber 1989; Ludwigia arcuta, Kuwabara et al 2003) that occurs under the control of ABA.…”
Section: Aba Functions In Bryophytesmentioning
confidence: 68%
“…Studies using ABA analogs lacking the 7'-, 8'-, or 9'-methyl groups showed that the 7'-methyl group is critical for bioactivity [33] . Flipping the cyclohexene ring around the chiral carbon produces the unnatural (-)-enantiomer, which has weak biological activity ( Figure 3B) [34] . Structural and functional analogs of ABA have been used to identify ABA-responsive genes, and some of these analogs are potential plant growth regulators [35,36] .…”
Section: Chemical Featuresmentioning
confidence: 99%